2019
DOI: 10.1002/mde.3098
|View full text |Cite
|
Sign up to set email alerts
|

Chief executive officer compensation, firm performance, and strategic coopetition: A seemingly unrelated regression approach

Abstract: Coopetition denotes the simultaneous cooperation and competition in a business relationship and is broader in depth and width than competition. This pioneering comparative study employs a seemingly unrelated regression system to investigate the impact of peer‐pay bias and pay‐for‐relative performance upon the highly controversial chief executive officer (CEO) pay. The analysis of the 21 Dow–Jones firms from 1992 to 2013 shows that the pay‐for‐performance relationship is contingent on the fit between CEO's stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
(111 reference statements)
1
9
1
Order By: Relevance
“…Therefore, it is imperative for researchers to use other methodology and a larger sample size to compare with our findings. For example, regression analysis, such as basic Ordinary Least Squares (OLS), more advanced Simultaneous Equations Systems (SES) [40] and Seemingly Unrelated Regressions (SUR), [41] can be used to find the causality and the significance of the factors that influence mental distress.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is imperative for researchers to use other methodology and a larger sample size to compare with our findings. For example, regression analysis, such as basic Ordinary Least Squares (OLS), more advanced Simultaneous Equations Systems (SES) [40] and Seemingly Unrelated Regressions (SUR), [41] can be used to find the causality and the significance of the factors that influence mental distress.…”
Section: Discussionmentioning
confidence: 99%
“…The level of compensation offered to chief executive officers (CEOs) and the relationship between executive pay and companies' financial performance are among the issues that the corporate governance literature deals with the most often. This topic was discussed in the last several decades (Jensen & Murphy, 1990;Mäkinen, 2005;Kato & Kubo, 2006;Brick et al, 2006;Iwu-Egwuonwu, 2010;Ozkan, 2011;Raithatha & Komera, 2016;Amarou & Bensaid, 2017;Yamina & Mohamed, 2017) as well as in recent years (Le et al, 2020;Lin & Shi, 2020;Dias et al, 2020;Amewu & Alagidede, 2021;Cui et al, 2021;Ding & Chea, 2021;Wang et al, 2021;Chen & Hassan, 2022;Kayani & Gan, 2022). Nonetheless, some authors have demonstrated empirically that the relationship between executive compensation and financial performance is significant and positive, while others have not found such a relationship at all.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it concentrates on emerging markets and concerns the relationship between executive pay and firm performance from the perspective of corporate governance principles adopted in Poland, where The Continental model is more suitable (Jerzemowska et al, 2013). The current literature on these relationships has been largely focused on The Anglo-American model (Ascherl et al, 2019;Le et al, 2020;Lin & Shi, 2020;Wang et al, 2021) or the Asia-Pacific countries (Farooque et al, 2019;Cui et al, 2021;Ding & Chea, 2021;Chen & Hassan, 2022;Kayani & Gan, 2022). Our decision is motivated by the lack of global consensus in the literature about these relationships and the non-existing current research across the Central Eastern European (CEE) region.…”
Section: Introductionmentioning
confidence: 99%
“…The present study attempts to extend the examination of the relationship between team performance and stock prices. As aforementioned, while most studies employed event analysis as their main methodology, recent studies argued for the use of a seemingly unrelated regression (Coates and Humphreys, 2008; Kim and Kim, 2020; Lin and Shi, 2020). Although the use of SUR is not a new econometric approach (Kakwani, 1967), it has become increasingly common due to its efficiency and ability to handle endogeneity issues (Kim and Kim, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the use of SUR is not a new econometric approach (Kakwani, 1967), it has become increasingly common due to its efficiency and ability to handle endogeneity issues (Kim and Kim, 2020). SUR is especially useful in examining the fluctuations of stock prices, where empirical evidence shows SUR can provide better accuracy and fit in understanding factors determining stock performance (Kim and Kim, 2020; Lin and Shi, 2020). The present study examines whether the performance of teams in the CSL is related to changes in stock price for the parent corporations that own the teams.…”
Section: Literature Reviewmentioning
confidence: 99%